Mapping Arabic Language Learning Methods: A Study of Madrasah Aliyah Pekanbaru - Anugrah Ilahi; Hakmi Wahyudi; Muhammad Fitriyadi; Izzatul Mellati; Nafisah Rahmah Nasution; Auli Rahman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
This study addresses the limited research on the implementation of Arabic language teaching methods in Madrasah Aliyah within the local context of Pekanbaru, Indonesia a gap rarely explored despite its significance for Islamic education quality improvement. The research aims to map and analyze the variety of Arabic language teaching methods practiced in these institutions and identify the challenges teachers face in applying them. Using a descriptive qualitative design, data were collected from two schools (Al-Munawwarah and Al-Ikhwan Madrasah Aliyah) involving six Arabic language teachers selected through purposive sampling based on teaching experience and subject relevance. Data were obtained through classroom observations and in-depth interviews and analyzed using Miles and Huberman’s interactive model. Findings reveal the application of an eclectic approach integrating the mubasyarah (direct), sam‘iyah syafawiyah (audio-oral), qira’ah (reading), and qawā‘id wa tarjamah (grammar-translation) methods within communicative and contextual learning frameworks. Digital media and gamification enhanced student engagement, though time constraints, differing abilities, and limited facilities remained significant barriers. Theoretically, this study contributes to the refinement of the eclectic pedagogy model for Arabic language instruction by contextualizing it within Indonesian madrasah settings. Practically, it provides strategic insights for policymakers and educators to develop adaptive, digital-integrated, and culturally responsive teaching frameworks that can enhance learning outcomes and motivation in Arabic education. In conclusion, strengthening teacher capacity and extending practice-based activities are crucial for sustainable improvement in Arabic learning at Madrasah Aliyah, contributing to the broader goal of advancing Islamic education quality in the digital era.